FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS PUDING BESAR KABUPATEN BANGKA TAHUN 2023 - Dania; Ardiansyah; Arjuna (Jurnal Ilmiah Keperawatan, 2024)
Non-Communicable Diseases (NCDs) have become a public health problem, globally and nationally. One of the NCDs that has attracted a lot of attention is Diabetes Mellitus. The aim of this research is to determine the factors related to the incidence of diabetes mellitus in the Puding Besar Health Center working area, Bangka Regency in 2023.This research was conducted using a cross sectional design and chi square test with results in the form of univariate and bivariate analysis tests. The research population is all people suffering from diabetes mellitus who live in the Puding Besar Health Center Working Area, Bangka Regency. The research sample was a portion of DM sufferers who lived in the Puding Besar Health Center Working Area from a research population of 95 respondents, taken using the Accidental Sampling technique.The results of the research prove that there is a relationship between the age factor p-value (0.004), p-value (0.001) and the incidence of Diabetes Mellitus in the Puding Besar Health Center Working Area, Bangka Regency in 2023.It is hoped that the suggestions from this research will help health workers carry out health promotion regarding Diabetes Mellitus and explain the risk factors for this disease. People are advised to always check their blood sugar, especially those aged ≥45 years and those who have a family history of diabetes mellitus. Exercise regularly to keep your body healthy and your metabolism running well.